Floral capitula and essential oil production analysis of chamomile (Chamomilla recutita) cultivars at different times of harvest - Matsushita, Milton Satoshi; Deschamps, Cícero; Corrêa Júnior, Cirino; Machado, Marília Pereira (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (páginas 484-490).